Job absorption and its relationship with the spirit of challenge of some volleyball coaches from the players' point of view - M. Afrah Baqir; Dr. Luma Sameer; Dr. Muslim Mohammed (physical education and sport sciences college for women/ Baghdad University, 2021)
The importance of the current study lies in the psychological preparation of coaches, their abilities and skills that can be measured for them and the possibility of being distinguished by them by coaches, and thus its reflection on their players because the players always derive challenge, enthusiasm and other psychological skills from their coaches and their characteristics that encourage players to perform well, The research problem is that there are basic and distinct features that should characterize the personality of the trainer and control most of his behaviors in different life situations because of their great and effective role in making him able to face the difficulties and challenges of life and at the same time lead to the development of his personality and as a result of the poor availability of information about job absorption. When volleyball coaches we realized The existence of a problem related to the measuring tool, as well as the existence of an ambiguous or unclear relationship between the job absorption and the spirit of challenge towards competition and the detection of such a characteristic among volleyball coaches, and the aim of the research is to identify the relationship between the absorption of career and the spirit of challenge for coaches of the Iraqi Premier League clubs in volleyball and prepare my standards Occupational absorption and the spirit of challenge for coaches of the Iraqi Premier League volleyball clubs, and identifying the two scales of the Iraqi Premier League volleyball coaches and the spirit of challenge for coaches of the Iraqi Premier League clubs in volleyball. 112) players from eight clubsThey are the (Army - Police - Industry - Erbil - South Gas - Al Daghara - Al Qasim - Al Bahri) club, then a sample of 56 players was randomly selected and they are club players (Army - Police - Qasim - Al Daghara). Challenge After addressing the results, it became evident that some coaches of the Iraqi Premier League clubs in volleyball enjoy a high level of professionalism and a spirit of challenge. There is a correlation between functional absorption and the spirit of challenge. Therefore, the researcher recommends working to develop the skills and abilities of coaches of the Iraqi Premier League clubs in volleyball and employing the skills and abilities possessed by each coach by improving their abilities and skills in the field of absorption (cognitive, intellectual, physical, emotional and social) by involving them in the counseling, cooperative and training courses conducted by the Union and the club In order to educate the trainer and his knowledge in all areas of concern, its main topic.